2017
DOI: 10.1007/s11920-017-0825-3
|View full text |Cite
|
Sign up to set email alerts
|

Trauma, PTSD, and the Developing Brain

Abstract: Purpose of review PTSD in youth is common and debilitating. In contrast to adult PTSD, relatively little is known about the neurobiology of pediatric PTSD, nor how neurodevelopment may be altered. This review summarizes recent neuroimaging studies in pediatric PTSD and discusses implications for future study. Recent findings Pediatric PTSD is characterized by abnormal structure and function in neural circuitry supporting threat processing and emotion regulation. Furthermore, cross-sectional studies suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
142
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(153 citation statements)
references
References 82 publications
4
142
1
6
Order By: Relevance
“…Another study showed that almost 25% of youth develop PTSD following exposure to interpersonal traumatic events and 10% following exposure to non-interpersonal traumatic events (Kolaitis, 2017). Besides classical PTSD symptoms, namely intrusion avoidance, negative alterations in cognitions and mood, and arousal and reactivity (American Psychiatric Association, 2013), adolescent PTSD could have some specificities compared to adult PTSD (e.g., Gerson & Rappaport, 2013;Herringa, 2017). At first place, symptoms expression could vary substantially, for example avoidant symptoms may be associated with restricted exploratory behavior, reduced participation in new activities or reluctance to pursue opportunities in adolescents (American Psychiatric Association, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study showed that almost 25% of youth develop PTSD following exposure to interpersonal traumatic events and 10% following exposure to non-interpersonal traumatic events (Kolaitis, 2017). Besides classical PTSD symptoms, namely intrusion avoidance, negative alterations in cognitions and mood, and arousal and reactivity (American Psychiatric Association, 2013), adolescent PTSD could have some specificities compared to adult PTSD (e.g., Gerson & Rappaport, 2013;Herringa, 2017). At first place, symptoms expression could vary substantially, for example avoidant symptoms may be associated with restricted exploratory behavior, reduced participation in new activities or reluctance to pursue opportunities in adolescents (American Psychiatric Association, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that symptoms related to intrusion, avoidance, negative affect, anhedonia, externalizing behavior, anxious, and dysphoric arousal best depict PTSD in adolescents (Cao, Wang, Cao, Zhang, & Elhai, 2017). In addition, there is heightened stress sensitivity of developing neural systems in adolescents, as well as delayed expression of the full effects of trauma exposure compared to adults (Herringa, 2017). Some structural and functional brain abnormalities were also found, like reduced ventro-medial prefrontal cortex volume and impaired recruitment of lateral prefrontal cortex, but not reduced hippocampal volume, and hyperactivity of the amygdala and insula as in adult PTSD (Herringa, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a substantial body of knowledge on the mental health and psychosocial consequences of disasters and conflict on children, including many good reviews [15,16]. Documented effects of loss and trauma on academic functioning are fairly strong [17,18]. Children in such adverse situations may react with fear, social withdrawal, a lack of concentration, sadness, depression, sleep problems, aggression, lost motivation for education, and dropping out of school.…”
Section: Psychosocial Consequences Of Disasters and Conflictmentioning
confidence: 99%
“…Connectivity of the default mode network was decreased with both the salience and attentional control networks that are implicated in threat detection and cognitive control, respectively. 87 Herringa 88 inferred that several factors may place traumaexposed children at increased risk for heightened stress sensitivity. These factors include hyperactivity in components of the salience network, including the dorsal ACC and amygdala, which monitor both internal and external threat cues, and increased anticorrelation or functional competition of the default mode network with salience and executive control networks.…”
Section: Limbic Circuitry In Relation To Ptssmentioning
confidence: 99%